An Analysis of Public Relations Strategies in Perception Management - Dodoo, Jennifer (UniMAC - GIJ, 2020)
The study was focused on analysing PR strategies in perception management. The study then set the following objectives in conducting the study. The first was to determine PR strategies that can be used to manage perceptions. The second was to explore how public perception can affect an organization’s reputation and the third was to find out way(s) of attaining a favourable public perception. The findings of the study indicates that community relations, CSR, social media management, media relations and others are among the PR techniques that could be used to control perception while social media management and community relations could be used to garner favorable public perception. The study recommended that individuals and organizations alike should take note of the concept of perception management if they cared about their public image.
THESIS